2019
DOI: 10.1289/ehp5564
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Bisphenol A and Parabens in a Neonatal Intensive Care Unit: An Exploratory Study of Potential Sources of Exposure

Abstract: Background:Newborns in neonatal intensive care units (NICUs) are in contact with a variety of medical products whose production might include synthetic chemicals with hormonal activity.Objectives:Our aim was to assess the content of bisphenol A (BPA) and parabens (PBs) and the hormone-like activities of a subset of medical products commonly used in NICUs in prolonged intimate contact with NICU newborns.Methods:Fifty-two NICU items were analyzed, determining the concentrations of BPA and PBs [methyl- (MeP), eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…While environmental exposure to BPA is continuous at a relatively low dose (Koch & Calafat, 2009; Vandenberg et al, 2007, 2010)—clinical (Calafat et al, 2009; Duty et al, 2013; Gaynor et al, 2018) and occupational (C. J. Hines et al, 2018; Ribeiro, Ladeira, & Viegas, 2017) environments can result in higher BPA exposures (Table 1) (Calafat et al, 2009; Duty et al, 2013; Gaynor et al, 2018; Huygh et al, 2015). BPA has been detected in 60% of neonatal intensive care unit (ICU) supplies, and experimental studies have identified estrogenic activity in >25% of extracts from these items (Iribarne‐Durán et al, 2019). Clinical exposure can result in heightened and/or prolonged exposure to BPA, particularly in neonatal and pediatric patients with an underdeveloped metabolic system (Calafat et al, 2009).…”
Section: Bisphenol‐amentioning
confidence: 99%
“…While environmental exposure to BPA is continuous at a relatively low dose (Koch & Calafat, 2009; Vandenberg et al, 2007, 2010)—clinical (Calafat et al, 2009; Duty et al, 2013; Gaynor et al, 2018) and occupational (C. J. Hines et al, 2018; Ribeiro, Ladeira, & Viegas, 2017) environments can result in higher BPA exposures (Table 1) (Calafat et al, 2009; Duty et al, 2013; Gaynor et al, 2018; Huygh et al, 2015). BPA has been detected in 60% of neonatal intensive care unit (ICU) supplies, and experimental studies have identified estrogenic activity in >25% of extracts from these items (Iribarne‐Durán et al, 2019). Clinical exposure can result in heightened and/or prolonged exposure to BPA, particularly in neonatal and pediatric patients with an underdeveloped metabolic system (Calafat et al, 2009).…”
Section: Bisphenol‐amentioning
confidence: 99%
“…Urinary BPA levels were also elevated in NICU babies exposed to phthalate-containing products, illustrating the challenge of combinatorial EDC exposures in the critical care setting ( 25 ). In a recent analysis of 52 common NICU items, the authors found that three-fifths of equipment contained BPA and fourth-fifths contained parabens ( 26 ). Critically, this study also demonstrated that extracts from the medical supplies altered endocrine activity in cell lines, with 25% of the extracts demonstrating estrogenic activity and 10% showing anti-androgenic activity ( 26 ).…”
Section: The Neonatal Intensive Care Unit As a Special Casementioning
confidence: 99%
“…In a recent analysis of 52 common NICU items, the authors found that three-fifths of equipment contained BPA and fourth-fifths contained parabens ( 26 ). Critically, this study also demonstrated that extracts from the medical supplies altered endocrine activity in cell lines, with 25% of the extracts demonstrating estrogenic activity and 10% showing anti-androgenic activity ( 26 ). Given the critical organizational role of hormones during development, these endocrine-disrupting activities raise concerns about long-term health risks.…”
Section: The Neonatal Intensive Care Unit As a Special Casementioning
confidence: 99%
“…Although environmental exposure to BPA occurs at a relatively low dose (Koch and Calafat 2009; Vandenberg et al 2007, 2010), occupational (Hines et al 2018; Ribeiro et al 2017) and clinical environments can result in exceedingly high BPA exposure (Calafat et al 2009; Duty et al 2013; Gaynor et al 2018; Huygh et al 2015; Testai et al 2016). Indeed, BPA was detected in 60% of neonatal intensive care unit (NICU) supplies, including items used for feeding, bandages, breathing support, intravenous and parenteral infusion (Iribarne-Durán et al 2019). Clinical exposure can also result in heightened and/or prolonged BPA exposure in young patients, due to an underdeveloped metabolic system (Calafat et al 2009).…”
Section: Introductionmentioning
confidence: 99%